Respondents’ Level of Education, Knowledge, Awareness, and Acceptability of Blue Ternate (Clitoria ternatea) as Alternative Medicine - Abance, Amity C.; Anglacer, Shallom D.; Soriano, Freddierick James A.; Umadhay, Andy Glen C.; Malaco, Amera C.; Besa, Adonis S. (Indonesian Journal of Multidiciplinary Research, 2021)
This study was carried out to determine the level of awareness among government employees and the level of acceptability of Blue Ternate (C. Ternatea) as an alternative medicine for hypertension, fever, and fatigue. The novelties in this research are (1) The Lambayong Government Employees’ acceptability on Clitoria Ternatea as alternative medicine, (2) awareness and assent of people on Clitoria Ternatea as alternative medicine, and (3) the relationship between factors influencing the respondents and the level of acceptability. A random sampling technique was utilized. The results implied that the Government Employees are informed about the Blue Ternate and somewhat aware of it as alternative medicine, especially in hypertension, fever, fatigue. As to the test of the relationship between factors that influenced the respondents and the level of acceptability, there is a significant relationship between them. Therefore, Clitoria Ternatea is aware and accepted by the people in the Sultan Kudarat area, The Philippines.